PENGGUNAAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Rafnidaroza Rafnidaroza (Adiba Aisha Amira, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (IRE) through the use of Wordwall media for fourth-grade students at SDN 17 Palaluar. The study employs a Classroom Action Research (CAR) method conducted in three cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observations, learning outcome tests, and student response questionnaires. The results showed an improvement in students' learning outcomes across cycles. In Cycle I, the average learning outcome score was 64, with a classical completeness of 33%; in Cycle II, it increased to 75, with 67% completeness; and in Cycle III, it reached 87, with 83% completeness. Students' responses to Wordwall media were also highly positive, as most students felt that the media was helpful and increased their learning motivation. Thus, the use of Wordwall media is proven effective in enhancing students' IRE learning outcomes.